The Relationship Between Sleep Duration and Blood Lipids Among Chinese Middle-Aged and Older Adults: Cross-Lagged Path Analysis From CHARLS - Ziwei Chen; Xia Zhang; Yanran Duan; Tingting Mo; Wenli Liu; Yilei Ma; Ping Yin (Frontiers Media S.A., 2022)
This study used data from the China Health and Retirement Longitudinal Study to investigate the temporal relationship between blood lipids and sleep duration in Chinese middle-aged and older adults. We used medical examinations and questionnaire data of 5,016 Chinese middle-aged and older adults (age 45+) in 2011 and 2015. Cross-lagged path analysis was performed to examine the bidirectional relationships between blood lipids and sleep duration. Sleep duration and lipids data were analyzed as continuous variables. Temporal relationships between sleep duration and HDL-cholesterol, LDL-cholesterol, total cholesterol, and triglycerides were different. Sleep duration was negatively associated with HDL-cholesterol 4 year later (β1 = −0.171, P = 0.005), and HDL-cholesterol was negatively associated with sleep duration 4 year later (β2 = −0.006, P = 0.002). Longer sleep duration was associated lower levels of LDL-cholesterol (β1 = −0.275, P = 0.097) and total cholesterol (β1 = −0.329, P = 0.096) 4 year later. There was a positive correlation between triglycerides and sleep duration. The path coefficient from triglycerides to sleep duration 4 year later (β2 = 0.001, P = 0.018) was greater than that from sleep duration to triglycerides 4 year later (β1 = 0.109, P = 0.847), with P = 0.030 for the difference between β1 and β2. In stratified analysis, we found that the strength and direction of the relationships may be related to age and BMI. Effects of sleep duration on blood lipids were only observed among participants aged <60 years, while the effect in the opposite direction was observed in older adults (age 60+), and the cross-lagged path coefficients were more significant in adults with BMI > 25.